Developing pragmatic competence in language teaching - Ibadullayeva Umida Xabibullayevna (Euro Asian Journal Publishing, 2024)
Successful language learning involves more than just grammar rules and vocabulary; understanding the pragmatic norms of a target language is also crucial. Lack of pragmatic competence in a target language can lead to misunderstandings and breakdowns in communication. It may result in speakers being perceived as impolite. Therefore, it is important for English as a Foreign Language (EFL) learners to focus on developing pragmatic competence to avoid such pitfalls. With the help of Communicative Language Teaching (CLT) method EFL learners can be acquainted with pragmatic competence on different speech act of using some effective strategies that will assist them to overcome their difficulties in successful communication. Accordingly, the main purpose of this research is to get EFL learners acquainted with pragmatic competence on the speech act of complaining using some effective strategies that will assist them to interact in real life settings
Keywords: Pragmatic competence; speech acts; target language